The Gotlandic box brooch from Fyrkat grave IV: A research into the casting technique and work methods associated with multi-piece brooches - Hedegaard, Ken Ravn (Danish Journal of Archaeology, 2016)
This study of the box-shaped brooch uses experimental archaeology in an attempt to gain more information about how these combination brooches were made. Some misunderstandings are addressed concerning the Fyrkat box brooch and Viking Age bronze casting in general. When trying to recreate the brooch, the four knot-shaped animals cast as one with the brooch throughout the work turned out to be the common denominator. They forced the original artisan to sacrifice an elaborate wax model when making the clay mould. Hollow models made of metal or solid bone could be used to produce this brooch only with difficulty. Again, due to the figural ornaments, a very complicated and time-consuming silver-plating technique was called for. Simple pure silver encasing was rendered nearly impossible. The very complex techniques used appear to have been the trademark of the artisan, designed to demonstrate his skill.